Barbapoux de Charles Malato, ou comment traduire le théâtre de contestation socjale - Ciesielka, Joanna; Kaczmarek, Tomasz (Translatoryka i Translacje. Przekład w XXI wieku. Wyzwania – możliwości – trendy, 2020)
The text Barbapoux written in 1900 by Charles Malato is an example of the protest theatre movement. The author of this dramma refers to several issues and problems of the epoche such as Dreyfus case in order to criticise the unjust social order and its representatives such as the army, the Catholic Church, the judiciary and the press. The text is full of rod games and numerous allusions to the current events of the time.The article highlights the examples of solutions applied in translation of the dramma into Polish. The focus is pointed on the translation of proper names (antroponyms and chrematonyms) as well as of selected idioms.